2017
DOI: 10.1371/journal.ppat.1006515
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis universal stress protein Rv2623 interacts with the putative ATP binding cassette (ABC) transporter Rv1747 to regulate mycobacterial growth

Abstract: We have previously shown that the Mycobacterium tuberculosis universal stress protein Rv2623 regulates mycobacterial growth and may be required for the establishment of tuberculous persistence. Here, yeast two-hybrid and affinity chromatography experiments have demonstrated that Rv2623 interacts with one of the two forkhead-associated domains (FHA I) of Rv1747, a putative ATP-binding cassette transporter annotated to export lipooligosaccharides. FHA domains are signaling protein modules that mediate protein-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 78 publications
0
53
0
Order By: Relevance
“…The ABC transporter Rv1747 is a virulence factor that has been implicated in transporting intermediates of the cell wall biosynthesis pathway across the Mtb membrane (14). Deletion of Rv1747 leads to Mtb growth defects in macrophages and infected mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ABC transporter Rv1747 is a virulence factor that has been implicated in transporting intermediates of the cell wall biosynthesis pathway across the Mtb membrane (14). Deletion of Rv1747 leads to Mtb growth defects in macrophages and infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…Dephosphorylation by PstP reverses this effect. Phase separationmediated clustering could potentially increase transport efficiency due to allosteric activity regulation, amplification of signals by selectively filtering substrates, and/or formation of a scaffold for interactions with additional components of the cell wall biosynthesis pathways (14). In this model, STPKs/PstP allow rapid and reversible activation/deactivation of Rv1747 on initial exposure to challenging environments in infected macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the role and metabolism of PIMs during M. tuberculosis infection and pathogenesis is still unclear, as different PIMs are recognized by different receptors triggering different host responses and outcomes. PIMs are downregulated in stationary phase (162), but it has been observed that the production of PIMs by M. tuberculosis is enhanced during infection in primary human macrophages (163). The latter result indicates that M. tuberculosis can adapt to the environment during infection by modulating its cell envelope composition (164)(165)(166)(167)(168).…”
Section: The Mannose-containing Glycolipid Familymentioning
confidence: 99%
“…The latter result indicates that M. tuberculosis can adapt to the environment during infection by modulating its cell envelope composition (164)(165)(166)(167)(168). That PIM expression levels during early stages of infection may be in part directly or indirectly involved in bacterial growth, virulence, and entry into persistence is still unclear; however, studies show that a PIM-hyperproducing M. tuberculosis strain ( Rv2623) is hypervirulent in vivo being unable to establish a chronic infection (163), while a PIMhypoproducing M. tuberculosis strain ( Rv1747) is attenuated in vivo in mice (169) ( Table 1).…”
Section: The Mannose-containing Glycolipid Familymentioning
confidence: 99%